2010
DOI: 10.1590/s1413-35552010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Influência da porção extensora do músculo glúteo máximo sobre a inclinação da pelve antes e depois da realização de um protocolo de fadiga

Abstract: Influences of the extensor portion of the gluteus maximus muscle on pelvic tilt before and after the performance of a fatigue protocolInfluência da porção extensora do músculo glúteo máximo sobre a inclinação da pelve antes e depois da realização de um protocolo de fadiga AbstractIntroduction: There is a lack of data in the literature for determining the influences of the extensor portion of the gluteus maximus muscle on pelvic tilting and, thus, on lumbar stability. Objectives: To assess the influences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the sagittal plane, the pelvis performs anteversion and retroversion movements so that lumbar lordosis increases when there is anteversion motion and when retroversion occurs lordosis is corrected (15,40). Therefore, Pilates ® works to ensure the pelvis is properly positioned, i.e., a neutral pelvis, due to its implications for the spine.…”
Section: Discussionmentioning
confidence: 99%
“…In the sagittal plane, the pelvis performs anteversion and retroversion movements so that lumbar lordosis increases when there is anteversion motion and when retroversion occurs lordosis is corrected (15,40). Therefore, Pilates ® works to ensure the pelvis is properly positioned, i.e., a neutral pelvis, due to its implications for the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Different initial muscular states (in terms of strength endurance), as well as different motor control strategies, maybe the cause of the individual differences found. It is known that in postural stabilization, different individuals show different motor activation patterns (Alvim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Yoo [15] achieved an increase in the anterior pelvic tilt by training the ventrally downwards pulling muscles in a patient with hypolordosis of the lumbar spine. Alvim et al [16] found an increase in the pelvic tilt with fatigue of the extensor portion of the M. gluteus maximus. Fundamental work was carried out by Klee [10], who was able to prove the influence of the aforementioned muscle groups on pelvic tilt through extensive intervention programs, and was thus able to refute the findings of Levine et al [17], who found no influence of the abdominal muscles on pelvic tilt.…”
Section: Introductionmentioning
confidence: 98%